THE EVALUATION OF DRAINAGE SYSTEMATBANK INDONESIA HOUSING COMPLEX PANCORAN, JAKARTA - Fajri Agma Syahranie; Sih Andayani (International Journal on Livable Space, 2022)
The Bank Indonesia housing complex located in Pancoran, South Jakarta has a lower topography than the surrounding area and due to the continued reduction in green open space, this can cause inundation as high as 10 cm – 60 cm which occurs on Jl.Rasamala Raya which is a main road. main access to the Bank Indonesia Complex. To overcome the problem of inundation, it is necessary to analyze the drainage system to determine the causes of inundation. Research requires data in the form of drainage systems, rainfall, existing canal dimensions and existing longitudinal storage capacity. Based on the calculation results, there are 7 channels that do not accommodate the planned 2-year flood discharge, namely 4 channels in the Bank Indonesia Complex area and 3 channels outside the Bank Indonesia Complex area, so 2 alternatives are implemented to overcome these problems, the first is to changes in channel dimensions and the second is the implementation of ecodrainage in the form of infiltration wells in the canal located in the Bank Indonesia complex. From the research results it is known that alternative 1 causes the total volume of water entering the long storage is increase from 3011 m3 in the existing conditions to 3030 m3. If implementing alternative 2, the inundation in the channel on Jl.Rasamala Raya can be overcome and the total volume of water entering the long storage has decreased from 3011 m3 in the existing conditions to 2940 m3